DEVELOPMENT OF A TRANSPARENT AND DEFORMABLE TWO DIMENSIONAL RADIOCHROMIC GEL DOSIMETER - Ataei, Pouria (My University, 2012)
Radiotherapy is used in many clinics to deliver a sufficient and uniform dose to the cancerous tumours while the dose to normal tissues is minimized. However, there is a possibility of missing the target volume due to patient set up/motion errors, or any fluctuation in treatment delivery. Therefore, accurate dose verification tools are essential to evaluate the delivered dose distribution of the designed treatment plan under realistic treatment conditions.
Current research is focused on developing 3D dose verification tools to record the complex dose distributions for quality assurance purposes and the evaluation of new treatment techniques. New and novel materials and read-out techniques suitable for use in hospitals are desirable. The objective of this research is to fabricate a transparent radiochromic gel dosimeter that may be used as quality assurance tool. Also, the fabricated gel must be analyzed using a simple optical read-out technique.
Gel dosimeters are gels that undergo some chemical changes upon irradiation as a function of absorbed dose. The absorbed dose may be recorded in three dimensions depending on the type of gel dosimeter. Radiochromic gels are dosimeters that change colour upon irradiation. A radiosensitive dye, leucomalachite green (LMG) is dissolved in a matrix material to record the dose distribution in 3D. LMG changes its colour upon irradiation, and has an absorbance band of 629nm.
In this research two different matrix materials were investigated: poly (vinyl alcohol) and gelatin. PVA was studied as the primary agent due to its adjustable mechanical strength and high transparency. PVA has also been studied to have a low diffusion rate when it was used as the matrix material in Fricke gel dosimeters [41]. Even though PVA had all the desired characteristics, fabricating a PVA based radiochromic dosimeter was not successful. Consequently, gelatin was used as the matrix material to fabricate a gelatin-based radiochromic dosimeter.
Using gelatin, highly transparent radiosensitive gels were successfully fabricated. The absorbencies of the irradiated gels were measured as a function of absorbed dose, using a 1D set up. After, the gels were formed into 5mm thick films and used as two-dimensional dose verification tools. The relationship between absorbance and absorbed dose for 1D measurement was obtained to be 0.00241± 0.00004 , and 0.0022 ± 0.00007 for 2D gels scaled to a thickness of 1 cm.
In all of the experiments the absorbance-dose relationships were similar in slopes, but there was an offset between different batches. The offset was 20% between the different experiments. Moreover, there was less than 5% error associated with the physical set up; the major source of error was due to the production and handling of the mixture, possibly due to the effects of inconsistent heating and UV light exposure.
The 2D gels were used to verify the dose distribution for the purpose of quality assurance. Six different complicated beams were delivered to the gels and their dose distributions were compared to their respective Pinnacle Calculated Planar (PCP) dose maps. The difference was found to be about 35% at worst; however, this error may be reduced by utilizing more sophisticated data processing methods. Nevertheless, the images were quite similar above 20Gy. Furthermore, the dose distributions recorded by the gels are qualitatively and quantitatively similar to the (PCP) dose map. Although the fabricated gel dosimeters show some promise as future tools for quality assurance purposes, they must go through many more stages of research to be used clinically.
Keywords: Gel Dosimetry; Radiochromic Dosimeter; Radiotherapy; Quality Assurance (QA) Leucomalachite Green (LMG); Poly(vinyl Alcohol) PVA; Gelatin; Micelle; Two dimensional; Medicine and Health Sciences; Physics; Medicine and Health Sciences